Panama : Detailed Assessments of Observance of Standards and Codes for Banking Supervision, Insurance Supervision, and Securities Regulation. (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Detailed Assessments of the Observance of Standards and Codes for Banking Supervision, Insurance Supervision, and Securities Regulation for Panama. The International Organization of Securities Commissions (IOSCO) assessment considered the securities regulatory framework, the powers, capabilities, and responsibilities of the authorities, as well as issues related to the securities markets, and the management of collective investment schemes and private pension funds. For assessment of insurance supervision, the existing laws on insurance, reinsurance, and captive insurance operations as well as specific regulation and anew draft insurance law were analyzed.